The Mosque as a Spiritual Service: Analyzing Experiential Marketing Strategy in Urban Religious Landscape - Muh Syahril Sidik Ibrahim Sidiq Ibrahim; Sarif Hidayatullah; Mauludi; Ahmad Faiz Khudlari Thoha (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Masjid Al-Ittihad Pakuwon Surabaya is one of the mosques located within a shopping mall that has successfully integrated da'wah services with an experiential marketing approach. This study aims to explore the application of experiential marketing elements in managing the mosque's da'wah services and to analyze the worshippers' experiences with the provided services and facilities. The experiential marketing elements focused on in this research include sense, feel, think, act, and relate, implemented to create a memorable experience for the worshippers. The research employs a qualitative method with a descriptive analysis technique. Data were collected through direct observations at the site, in-depth interviews with worshippers, and documentation of the mosque's programs. Data analysis was conducted to understand how each element of experiential marketing is applied to support the mosque's function as a place of worship and a center for social activities. The results indicate that Masjid Al-Ittihad has successfully provided comfort through cleanliness, organized layouts, and facilities such as lockers, children's play areas, a library, and free meals every Friday. Worshippers reported positive experiences from various service innovations, ranging from ease of access to an atmosphere that supports spiritual focus during worship. Moreover, the mosque actively integrates relevant da'wah approaches through religious studies, collaborations with religious organizations, and the use of technology to enhance interaction and engagement with worshippers. By implementing experiential marketing, Masjid Al-Ittihad has successfully met the spiritual and social needs of its worshippers, establishing itself as a model for adaptive and innovative mosque management.